Primary Cutaneous Anaplastic Large Cell Lymphoma: A Rare Case Report in a Young Soldier (Journal of Armed Forces Medical College, Bangladesh, 2022)
Primary cutaneous anaplastic large cell lymphoma (C-ALCL) usually presents with scaly patches or plaques and nodular skin lesion. Most people with C-ALCL have indolent (i.e., chronic, slow growing) lymphomas which are treatable and curable. Histologically cutaneous anaplastic large cell lymphoma is diffuse, non-epidermotropic with anaplastic large lymphoid cells. Immunohistochemically most of the tumor cells express CD30 antigen and prognosis is good. Excision of the lesion followed by radiotherapy and/or low dose methotrexate are the treatment of choice. The present study reports a rare case of 30-year-old-man presenting with multifocal papulonodular lesions in the right forearm and biopsy confirmed that the case is cutaneous anaplastic large-cell lymphoma. He was treated with low dose of methotrexate and patient became completely cured without any residual disease.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 46-48